2013
DOI: 10.1111/apha.12094
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of an x‐ray contrast medium on renal T2*/T2MRI as compared to short‐term hyperoxia, hypoxia and aortic occlusion in rats

Abstract: T2 * mapping corroborates data previously obtained with invasive methods and demonstrates that CM injection affects renal medullary oxygenation. CM-induced T2 * decrease in OM was small vs. hypoxia and aortic occlusion. T2 * decrease obtained for hypoxia was more pronounced than for AO. This indicates that T2 * may not accurately reflect blood oxygenation under certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…13 In animal models, several investigators have utilized BOLD MRI to demonstrate that breathing pure oxygen increases oxygenation in all renal compartments. 4,12 Pohlmann et al 4 confirmed these findings in pigs with simultaneous BOLD MRI measurements and direct measurements of pO 2 performed in the same kidney. Although the data are not entirely consistent, most BOLD MRI studies in humans have demonstrated that breathing 100% oxygen increases intrarenal oxygenation in the medulla but not in the cortex, suggesting nonsaturation of renal medullary oxygenation under physiologic conditions.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…13 In animal models, several investigators have utilized BOLD MRI to demonstrate that breathing pure oxygen increases oxygenation in all renal compartments. 4,12 Pohlmann et al 4 confirmed these findings in pigs with simultaneous BOLD MRI measurements and direct measurements of pO 2 performed in the same kidney. Although the data are not entirely consistent, most BOLD MRI studies in humans have demonstrated that breathing 100% oxygen increases intrarenal oxygenation in the medulla but not in the cortex, suggesting nonsaturation of renal medullary oxygenation under physiologic conditions.…”
mentioning
confidence: 77%
“…3 Consistent with these observations, inhalation of pure nitrogen or 10% oxygen reduced oxygenation in all renal compartments in experimental animals. 4,11,12 Breathing 100% oxygen increases arterial plasma pO 2 , but has a minimal effect on the deoxyhemoglobin/ oxyhemoglobin ratio in healthy subjects since hemoglobin oxygen saturation is nearly complete. However, inhalation of …”
Section: Inspiratory Oxygen Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…R2* (=1/T2*) relaxation rate has been used as BOLD MRI parameter based on our previous reports 8, 9 . Others have also concluded that R2* changes post-iodinated contrast are reflective of renal oxygenation 16 . The renal injury after iodinated contrast was confirmed using uNGAL.…”
Section: Introductionmentioning
confidence: 99%